Semiotics Analysis of Modern Drink Advertisements on the Palangkaraya Cafe Instagram Account - Sutiah; Imam Qalyubi; Zaitun Qamariah (Channing : Journal of English Language Education and Literature, 2023)
This research paper titled "Semiotic Analysis of Modern Drink Advertisements on The Palangkaraya Cafe Instagram Account" delves into the realm of modern drink advertisements in the digital age. It explores the significance of semiotics in understanding the hidden messages conveyed by advertisements in the context of cafes. The study aims to answer two main research questions: What kinds of signs exist in modern drink advertisements, and what meanings are conveyed by these signs? The research employs a qualitative descriptive approach, utilizing interviews and documentation as data collection methods. The study's primary focus is on three cafes in the Palangkaraya area: Taguk Ha Cafe, Nakaya Cafe, and Yomi Cafe, with a specific emphasis on modern drink advertisements from their Instagram accounts. Data analysis follows a systematic process, including data reduction, data display, and conclusion drawing/verifying. The researcher uses Charles Sanders Peirce's semiotic theory to analyze the signs in the advertisements, distinguishing between icons, indices, and symbols. The result of this research shows In essence, language and symbolic signifiers in advertising transcend the boundaries of brand communication. They become the conduits through which desires are kindled, emotions are stirred, and aspirations are awakened in the audience. Whether through carefully crafted language or the strategic use of symbols, advertisers have at their disposal a rich palette of tools to engage consumers on a profound and deeply meaningful level, thereby forging connections that extend beyond the realm of commerce.